2015
DOI: 10.1111/liv.12908
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of platelet count are different in patients with compensated and decompensated cirrhosis

Abstract: Platelet count in cirrhosis is associated mainly to spleen volume, although portal hypertension as estimated by HVPG and liver function plays a significant role in compensated patients. H-TPO and the proportion of patients with P-TPO > H-TPO were associated to the presence and severity of liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In compensated liver cirrhosis, spleen size correlated with platelet counts 16,17 and was directly proportional to the phagocytic activity of the spleen 18 ; therefore, we used spleen size to evaluate the degree of hypersplenism. In the current study, spleen volume significantly decreased approximately 1 year after starting antiviral therapy, suggesting that the degree of hypersplenism decreased 1 year after the start of antiviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In compensated liver cirrhosis, spleen size correlated with platelet counts 16,17 and was directly proportional to the phagocytic activity of the spleen 18 ; therefore, we used spleen size to evaluate the degree of hypersplenism. In the current study, spleen volume significantly decreased approximately 1 year after starting antiviral therapy, suggesting that the degree of hypersplenism decreased 1 year after the start of antiviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the influences of etiology and sex were only moderate but that of severity was marked. Indeed, VNT prevalence, platelets and LSM are strongly related to liver severity 13 . This results in the reduction of the performance of NITs in severe CLD.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…BMSC transplantation, as a new technology for repairing regenerated damaged organs, has become a research hotspot for stem cell transplantation due to the advantages of convenient collection, low rejection, safety and reliability, and low cost[ 23 , 24 ]. BMSCs can replace damaged hepatocytes by inducing differentiation into hepatocytes in severe liver disease, improve function of the damaged liver, and bring new hope for the treatment of cirrhosis[ 25 , 26 ]. In our previous study, ABMI for patients with DLC and acquired immunodeficiency syndrome significantly prolonged survival.…”
Section: Discussionmentioning
confidence: 99%